Development of Electronic Student Worksheets Based on the Science, Environment, Technology, and Society Learning Model on Sound and Light Waves Topic - Maryam, Siti; Rizal, Rahmat; Suhendi, Herni (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
The objectives of the study were (1) to describe the level of validity and practicality of electronic student worksheet based on Science, Environment, Technology, and Society (SETS) learning model on the material of sound and light waves. The research method used was Research and Development (R&D) with the ADDIE model. The research population consisted of 6 classes of the 11th-grade mathematics and science program (MSP) in MAN 3 Tasikmalaya with a total of 211 students, and a sample of 138 students was taken using the cluster random sampling technique. Validation of the feasibility was carried out by material, media, and learning experts using Aiken’s index, which each produced values ​​of 0.87, 0.84, and 0.89, with an average of 0.86 (very high validity). The practicality test showed results of 91.65% of students and 100% of educators (very practical). The results of the development of this electronic student worksheet are expected to be an alternative media and technology-based teaching material to help effective learning activities and provide meaningful learning experiences for students so that they can achieve learning goals optimally.